Using Key Distance to Clarify a Theory on the SNARC. (January 2016) - Schiller, Florian; Eloka, Owino; Franz, Volker H.
The most prominent explanation for the spatial numerical association of response codes (SNARC) effect is the direct mapping account (DMA). The DMA assumes that (a) numbers are represented on a mental number line, (b) this mental number line is mapped to external space, and (c) the better the mapping location corresponds to the response location, the faster the response. The DMA leaves open whether a variation of response locations can (ceteris paribus) influence the location to which numbers are mapped in external space. In order to investigate this question, we varied response key distance during a standard parity judgment and a magnitude judgment task. We found that even drastic manipulations of response key distance did not modulate the SNARC effect. Power and meta-analyses show that this null effect is not due to insufficient statistical power or a poor experimental setup. Thus, our results indicate that, in order for the DMA to explain the SNARC effect, it must assume that the mapping from the mental number line to external space is anchored to response location. For future research, our results suggest that it is not necessary to control the horizontal separation of the response keys in basic SNARC experiments.